KONSEP PENGASUHAN MINDFULNESS DAN APLIKASINYA DALAM MENANAMKAN NILAI KEAGAMAAN PADA ANAK USIA DINI - Rizkiana, Afitria (TARBAWI:Journal on Islamic Education, 2023)
Mindfulness Parenting is an approach to child-rearing that combines the concept of mindfulness, which is the state of being fully aware and present in the current moment, with positive and empathetic parenting principles. Early childhood is a critical period in individual development. During this stage, fundamental values and beliefs begin to be ingrained in a child's mind and behavior. Religion and spirituality play a significant role in shaping a child's value system and morality. Therefore, this article provides an overview of how the concept of mindfulness parenting and its application can be used to instill religious values in young children. The prevailing paradigms surrounding mindfulness parenting will be the focus of study and analysis in this article, progressing from theoretical concepts to practical applications. Mindfulness Parenting offers an effective approach to instilling religious values in young children. By combining awareness and full presence in parenting, parents or caregivers can help children understand, internalize, and apply religious values in their daily lives